MRI-guided focused ultrasound for treating Parkinson’s disease with human mesenchymal stem cells - Sheng-Kai Wu; Chia-Lin Tsai; Aisha Mir; Kullervo Hynynen (Scientific Reports)
Abstract Parkinson’s disease (PD) is a progressive disorder that affects the nervous system and causes regions of the brain to deteriorate. In this study, we investigated the effects of MR-guided focused ultrasound (MRgFUS) for the delivery of human mesenchymal stem cells (MSCs) on the 6-hydroxydopamine (6-HODA)-induced PD rat model. MRgFUS-induced blood-brain barrier (BBB) permeability modulation was conducted using an acoustic controller with the targets at the striatum (ST) and SN. Human MSCs were injected immediately before sonication. Here, we show that we can deliver human MSCs into Parkinsonian rats through MRgFUS-induced BBB modulation using an acoustic controller. Stem cells were identified in the sonicated brain regions using surface markers, indicating the feasibility of MSC delivery via MRgFUS. MSCs + FUS treatment significantly improved the behavioural outcomes compared with control, FUS alone, and MSCs alone groups (p < 0.05). In the quantification analysis of the TH stain, a significant reservation of dopamine neurons was seen in the MSCs + FUS group as compared with the MSCs group (ST: p = 0.03; SN: p = 0.0005). Mesenchymal stem cell therapy may be a viable treatment option for neurodegenerative diseases such as Parkinson’s. Transcranial MRgFUS serves as an efficacious and safe method for targeted and minimally invasive stem cell homing.